2010
DOI: 10.1002/jbmr.120
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of human bone marrow stromal cell proliferation and differentiation capacity by glucocorticoid receptor and AP-1 crosstalk

Abstract: Although marrow adipocytes and osteoblasts derive from a common bone marrow stromal cells (BMSCs), the mechanisms that underlie osteoporosis-associated bone loss and marrow adipogenesis during prolonged steroid treatment are unclear. We show in human BMSCs (hBMSCs) that glucocorticoid receptor (GR) signaling in response to high concentrations of glucocorticoid (GC) supports adipogenesis but inhibits osteogenesis by reducing c-Jun expression and hBMSC proliferation. Conversely, significantly lower concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
57
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(64 citation statements)
references
References 42 publications
(31 reference statements)
4
57
0
1
Order By: Relevance
“…This is another important finding because divergent effects of PDGFR have been reported in MSC osteogenic differentiation. Although PDGF was reported to have positive or negative effects on bone marrowderived mesenchymal progenitor cell differentiation in vitro (51,52), PDGFR signaling was shown to promote bone formation in vivo (53)(54)(55). Consistently, we found that inhibition of PDGFR and FGFR abrogated hMSC osteogenic differentiation induced by the mutant Cbl, which strongly supports a role for these receptors in hMSC osteogenic differentiation.…”
Section: Discussionsupporting
confidence: 83%
“…This is another important finding because divergent effects of PDGFR have been reported in MSC osteogenic differentiation. Although PDGF was reported to have positive or negative effects on bone marrowderived mesenchymal progenitor cell differentiation in vitro (51,52), PDGFR signaling was shown to promote bone formation in vivo (53)(54)(55). Consistently, we found that inhibition of PDGFR and FGFR abrogated hMSC osteogenic differentiation induced by the mutant Cbl, which strongly supports a role for these receptors in hMSC osteogenic differentiation.…”
Section: Discussionsupporting
confidence: 83%
“…Multiple studies suggest that when ASC fate is committed to the adipogenic pathway, osteogenesis is concomitantly down regulated, consistent with observations in BMSCs [25,32]. This balance is suggested to be partly modulated by the presence and amount of glucocorticoid, the glucocorticoid receptor pathway activity, crosstalk with the Jak/STAT3 pathway, and the subsequent activation of the AP-1 pathway [33,34]. Other studies have suggested that an inverse relationship exists between donor age and ASC osteogenesis [35], and that ASCs from male donors exhibit increased osteogenic potential compared to ASCs from female donors in vitro [36].…”
Section: Discussionsupporting
confidence: 71%
“…In the current study, JNK signaling stimulated Runx2 activity, which had been reported to promote osteogenic differentiation of BMSCs (Cárcamo-Orive et al 2010;Huang et al 2012). Activation of the Wnt5a/Ror2 pathway by interleukin (IL)-1β had been reported to promote mesenchymal stem cell differentiation into osteoblasts (Sonomoto et al 2012).…”
Section: Discussionmentioning
confidence: 85%